Factors Determining Wage Differentials in the Americas - Jecchinis, Chris; Harris, T. (Relations industrielles / Industrial Relations, 1974)
This paper reviews factors that determine wage differentials in the developing and the developed countries of the Americas and considers consequent policy questions.